Effectiveness of Pre PRP Injection and Post Elevation Flap at Extended Random Flap Rat Skin - Nugroho, Thomas Eduardus Sudrajat Wahyu; Rizaliyana, Sitti; Perdanakusuma, David S (Folia Medica Indonesiana, 2020)
Background:Closure of the defect with a random skin flap is constrained by the extent of the defect area. Several studies have shown the benefits of administration of PRP (Platelet Rich Plasma) in random skin flap. The purpose of this study is to compare the effect of PRP injection given before flap elevation, after flap elevation and control on the extended random skin flap procedures in rats. Methods: This research is experimental with randomized post test only control group design (n = 27, divided into 3 treatment groups) that compare the effectiveness of PRP injection 24 hours prior to the elevation of the flap, after the elevation of the flap, and control in the extended random skin flap in rats. Random skin flap is made in the ratio 1: 5 on the rat skin. Measurement of viable area were observed on days 1, 7 and 14. Results: There were significantly increased viability of random skin flap on the group with PRP injection 24 hours prior flap elevation compared to other group of treatment. The average of viability on day first 39%±13% ;42%±34%; 62%±14%. On day 7th24%±13%; 36%±26%; 62%±12%.On day 14th16%±15%; 28%±22%; 60%±11%. Conclusion: Injection of PRP on extended random skin flap on rat 24 hours before flap elevationincrease viability of the flap compared to control group and group which receive PRP injection on extended random flap on rat skin after elevation of the flap. Viability increased due to angiogenesis stimulation after PRP injection.